Correlation between Mortality of COVID-19 Patients with Hypertension and Thorax Radiography Treated in the Intensive Care Unit of Dr. Moewardi Hospital - Nurhidayati, Faiza Salsabila; Soewondo, Widiastuti; Dewi, Ratih Tri Kusuma; Putro, Prasetyo Sarwono (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Coronavirus 2019 or COVID-19, caused by the new SARS-CoV2 virus, has become a pandemic and attacked more than 200 countries, including Indonesia. The most comorbid disease in COVID-19 patients was hypertension. Chest radiography can predict prognosis and mortality in COVID-19 cases and one of the methods that can be used for chest radiographic assessment is the Brixia Score, specifically designed for COVID-19 patients to measure and analyze the severity of lung abnormalities in patients with COVID-19. This study aimed to find the correlation between the mortality of COVID-19 patients with hypertension and chest radiography using the Brixia Score treated in the intensive care unit (ICU) of Dr. Moewardi Hospital.Subjects and Method: This study used an analytic observational study with a cross-sectional approach. The subjects were 84 COVID-19 patients with hypertension who met the exclusion and inclusion criteria. The independent variable is chest radiography and dependent variable is mortality. Sampling was collected by purposive sampling and the data obtained were analyzed using the contingency coefficient test.Results: There was a significant correlation between the mortality of COVID-19 patients with hypertension and chest radiography as assessed using the Brixia Score (p<0.001). The youngest patient was 20 years old and the oldest was 87 years old.Conclusion: There was a correlation between the mortality of COVID-19 patients with hypertension and chest radiography treated in the ICU RSUD Dr. Moewardi, Surakarta.Keywords: COVID-19, mortality, hypertension, chest radiography, Brixia Score, intensive care unitCorrespondence: Widiastuti Soewondo. Faculty of Medicine Universitas Sebelas Maret Surakarta. Jl. Ir. Sutami 36A, Surakarta 57126, Indonesia. Email: Widiastuti.sprad56@staff.uns.ac.id. Mobile: 082134368592.Indonesian Journal of Medicine (2022), 07(03): 269-277https://doi.org/10.26911/theijmed.2022.07.03.03